Vulnerability of p otential s oil e rosion and r isk a ssessment at h illy f arms using InSAR t echnology - Nasidi, Nuraddeen Mukhtar; Wayayok, Aimrun; Abdullah, Ahmad Fikri; Mohd Kassim, Muhamad Saufi (جامعة الوادي - university of eloued, 2020)
Soil erosion is a serious environmental challenge which is persistently diminishing the available land resource in many places around the world, particularly the highlands areas. The traditional approach of estimating the magnitude of erosion is tedious, costly, and considerably time consuming. This study is aimed at assessing the risk level associated with soil erosion at hilly areas of Cameron Highlands through Interferometric Synthetic Aperture Radar (InSAR). The digital elevation model with 5 m resolution was utilized to generate the slope map for the highlands. Soil erosion rates was estimated using universal soil loss equation, while information about land use and cover were sourced from relevant government agencies. The analysis shows that, there was about 217.5 km2 (30.5%) of highlands fall under severely steep zone with slope ≥ 45-degree. Moreover, erosion risk assessment indicated that; 66.3%, 11.4%, 11.7% and 10.8% of the severe sloppy lands are classified as very low to high susceptible to soil erosion respectively. In general, the risk of soil erosion is relatively low and could be attributed to large vegetation coverage despite steep slopes. However, there is need to deploy a control measures to reduce soil disturbance activities on highlands with extremely steep slope as a proactive measures to minimize the effect of potential soil erosion
Article
Keywords: Erosivity; Soil Erodibility; GIS; USLE; Cameron Highlands